Ontogenesis in Iqbāl and Goethe: Die to Become - Aguirre Martínez, Guillermo (Anaquel de Estudios Árabes, 2020)
This paper reveals a serial of correspondences between Iqbāl’s and Goethe’s thought. Both authors approach with their works the Western and the Eastern imaginary. We will study all these aspects since the next terminology: a desire’s poetics. The meaning of the light, in relation with a mystical participation, is another of the axis points of this paper.